ANALYSIS OF ISLAMIC FINANCIAL LITERACY LEVEL ON MSME PRACTITIONERS IN PEMATANG SERAI VILLAGE - Chrisna, Heriyati; Hernawaty, Hernawaty; Noviani, Noviani (Proceeding International Seminar of Islamic Studies, 2023)
This research was conducted in Pematang Serai Village, Langkat Regency. Respondents of this study were MSME practitioners who were mostly customers of the Bumdes Mozaik Syariah Savings and Loan Business Unit in Pematang Serai Village. From the results of research using the financial literacy model formulated by Chen Volpe (1998) with measurements in 4 aspects it was found that the level of Islamic financial literacy in Pematang Serai Village UMKM practitioners included in the low category of 56.46%. The lowest aspect is the aspect of sharia investment, with the score obtained is 48.72%, while the highest aspect is the basic aspect of Islamic financial knowledge by obtaining a score of 66.4%. Suggestions that can be given to Pematang Langkat Village UMKM Practitioners to increase Islamic financial literacy are setting aside time to attend seminars or workshops on Islamic finance, for the village government is expected to facilitate activities related to efforts to increase Islamic financial literacy and the most expected is the OJK party Can go down to villages so that Islamic financial literacy in the village community, especially SMEs in the village can increase.